Outflow of Talents or Exodus? Evidence on youth emigration from EU’s peripheral areas - Maleszyk, Piotr (REGION, 2021)
Human-capital migration and its consequences for regional development are among the central issues discussed in migration and regional literature, while a growing interest has been recently observed in student migration as a driver of brain exchange between regions and countries. Furthermore, poor sending areas are often considered to be severely affected by the brain drain. Nevertheless, firm empirical evidence on the degree of the human-capital selectivity of youth migration is actually scarce due to measurement and methodological limitations. This paper sheds some light on human-capital redistribution across regions and countries by estimating the intensity and human-capital selectivity of youth emigration from poor and peripheral EU areas in Poland. A survey of 10 thousand secondary school graduates allowed an analysis of mobility patterns in relation to school-leaving exam results being a proxy for human capital, as well as to sex, type of school and former place of residence. This study revealed, that roughly 20% of graduates leave their home region, although migration rates across the youth characteristics followed by the results of logit regression model confirm that migration outflows, and particularly interregional moves, are a highly selective phenomenon. With regard to international mobility, student migration is positively selected as well, but economic migration among graduates electing not to continue education turns out to be adversely selected. Overall, the brain drain on EU’s peripheral areas in Poland with respect to the emigration of secondary-school graduates should be regarded as a selective outflow of most talented graduates to the leading academic centres, rather than massive migration of all graduates.